2011
DOI: 10.1007/s11239-011-0663-9
|View full text |Cite
|
Sign up to set email alerts
|

Does anti-tnf therapy cause any change in platelet activation in ankylosing spondylitis patients?

Abstract: Recently, it has been reported that ankylosing spondylitis (AS) was characterised by endothelial dysfunction and the development of atherosclerotic complications. In this study, we evaluated platelet and endothelial activation parameters in AS patients. Fiftynine AS patients and 22 healthy controls were included. The clinical features and acute phase parameters were evaluated. In all patients and healthy controls, platelet-monocyte complexes (PMC), platelet-neutrophil complexes, basal and ADP-stimulated P-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Fifteen studies were further excluded for the lack of usable data, and two additional studies were identified though an updated literature search on September 2, 2020 (Supplementary Figure S1). Therefore, 14 published observational studies were finally included (Kisacik et al, 2008;Wang et al, 2008;Yazici et al, 2010;Nalbant et al, 2011;Orum et al, 2012;Boyraz et al, 2014;Bozan et al, 2016;Sezgin et al, 2017;Huang et al, 2018;Tang et al, 2018;Enginar and Kacar, 2019;Al-Osami et al, 2020;Liu et al, 2020;Zhuang et al, 2020). Supplementary Table S2 showed the main characteristics of those observational studies included in the meta-analysis.…”
Section: Significantly Increased Platelet Count In As Patientsmentioning
confidence: 99%
“…Fifteen studies were further excluded for the lack of usable data, and two additional studies were identified though an updated literature search on September 2, 2020 (Supplementary Figure S1). Therefore, 14 published observational studies were finally included (Kisacik et al, 2008;Wang et al, 2008;Yazici et al, 2010;Nalbant et al, 2011;Orum et al, 2012;Boyraz et al, 2014;Bozan et al, 2016;Sezgin et al, 2017;Huang et al, 2018;Tang et al, 2018;Enginar and Kacar, 2019;Al-Osami et al, 2020;Liu et al, 2020;Zhuang et al, 2020). Supplementary Table S2 showed the main characteristics of those observational studies included in the meta-analysis.…”
Section: Significantly Increased Platelet Count In As Patientsmentioning
confidence: 99%
“…In our study, E-selectin levels did not differ significantly in both AS and RA patients compared with control group. The cause of subclinical atherosclerosis may be due to platelet parameters, which are another important component in the atherosclerotic process because AS patients have normal endothelial function (19). We also found no significant difference in E-Selectin levels between all patients with rheumatic disease and control group.…”
Section: Discussionmentioning
confidence: 45%
“…In that study, it was disclosed that anti-TNF-α infusion led to a decrease in serum sE-selectin and sVCAM-1 levels, even if they did not achieve statistical significance [33]. Although some authors also reported a significant reduction in VCAM-1 expression [34] or E-selectin [35] after anti-TNF-α treatment, others did not find any difference in the concentration of these molecules following TNF-α blockade [36,37]. These apparently contradictory results may be due to the period of time elapsed between the assessment of these biomarkers and the time of anti-TNF-α administration.…”
Section: Discussionmentioning
confidence: 99%